EFEK HIPOGLIKEMIK EKSTRAK ETANOL BATANG KARAMUNTING (MELASTOMA MALABATHRICUM) TERHADAP KADAR GULA DARAH DAN PERUBAHAN STRUKTUR MIKROANATOMI PANKREAS MENCIT (MUS MUSCULUS L.) DIABETESI - Wulandari, Anita; Sudiastuti, Sudiastuti; Sudrajat, Sudrajat (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
This study aims to determine the effect of ethanol extract of stem Karamunting to improve pancreatic microanatomy structure diabetic mice. The study design used was completely randomized design (CRD which is consisting of negative group control, positive control, and the group treated with 100,250 and 500 mg/kg weigth body dose of karamunting stem extract for 28 days. Blood glucose levels in mice then measured using the blood sugar measuring device gluco meter (Nesco Multicheck) Measurements were taken on day 7 after administration of alloxan. On the 28th day, treatment three at a dose of 500 mg / kg / day showed that the pancreatic cells as the cells in the positive control (normal), whereas treatment 1 at a dose of 100 mg / kg / day and treatment 2 doses 250 mg / kg / day is equal to the negative control. The results showed that the sample extraction rod microanatomy Karamunting able to improve the structure of the pancreas of mice at a dose of 500 mg / kg / day.